Seaman's journal : on the trail with Lewis and Clark - Eubank, Patti Reeder (Ideals Children's Books, 2002)
Seaman, the Newfoundland dog belonging to Meriwether Lewis, keeps an account of their adventures during the journey to the Pacific.